Selective imaging of quorum sensing receptors in bacteria using fluorescent Au nanocluster probes surface functionalized with signal molecules - Mukherji, Ruchira; Samanta, Anupam; Illathvalappil, Rajith; Chowdhury, Somak; Prabhune, Asmita; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2013)
Fluorescent ultrasmall gold clusters decorated with bacterial quorum sensing signal molecules, acyl homoserine lactone, are synthesized. These fluorescent probes are found to have emission in the near-infrared spectral region advantageous for bioimaging. Imaging studies using different. strains of bacteria with and without acyl homoserine lactone receptors with the aid of confocal microscopy have shown that the probe interacts preferentially with cells possessing these receptors. This indicates that, with appropriate surface functionalization, the Au clusters can be used for receptor specific detection with enhanced selectivity.
Keywords: Au nanoclusters; Biosensor; fluorescence imaging; quorum sensing

Sequence and structure-based comparative analysis to assess, identify and improve the thermostability of penicillin G acylases - Panigrahi, Priyabrata; Chand, Deepak; Mukherji, Ruchira; Ramasamy, Sureshkumar; Suresh, C. G. (Journal of Industrial Microbiology & Biotechnology, 2015)
Penicillin acylases are enzymes employed by the pharmaceutical industry for the manufacture of semi-synthetic penicillins. There is a continuous demand for thermostable and alkalophilic enzymes in such applications. We have carried out a computational analysis of known penicillin G acylases (PGAs) in terms of their thermostable nature using various protein-stabilizing factors. While the presence of disulfide bridges was considered initially to screen putative thermostable PGAs from the database, various other factors such as high arginine to lysine ratio, less content of thermolabile amino acids, presence of proline in beta-turns, more number of ion-pair and other non-bonded interactions were also considered for comparison. A modified consensus approach designed could further identify stabilizing residue positions by site-specific comparison between mesostable and thermostable PGAs. A most likely thermostable enzyme identified from the analysis was PGA from Paracoccus denitrificans (PdPGA). This was cloned, expressed and tested for its thermostable nature using biochemical and biophysical experiments. The consensus site-specific sequence-based approach predicted PdPGA to be more thermostable than Escherichia coli PGA, but not as thermostable as the PGA from Achromobacter xylosoxidans. Experimental data showed that PdPGA was comparatively less thermostable than Achromobacter xylosoxidans PGA, although thermostability factors favored a much higher stability. Despite being mesostable, PdPGA being active and stable at alkaline pH is an advantage. Finally, several residue positions could be identified in PdPGA, which upon mutation selectively could improve the thermostability of the enzyme.
Keywords: Alkalistable; beta-lactam antibiotics; Consensus approach; Disulfide bridge; Ion pairs; Penicillin acylase; Thermostability